Scale without substance: Rethinking the future of shariah economics in Bangladesh - Mohammad Sahabuddin (Journal of Islamic Economic Insights, 2026)
Bangladesh has quietly become one of the most significant Islamic finance jurisdictions in the world, with Shariah-based banks now contributing nearly a third of national banking deposits. However, the depositor-confidence crisis and acute liquidity stress that engulfed several large Islamic banks in Bangladesh between 2022 and 2024 exposed a deeper tension that features between the distinct existence or scale and the substantive ethical objectives of the maqāṣid al-sharīʿah. This opinion article argues that Islamic finance in Bangladesh has largely expanded as “interest-free banking” in a conceptual sense, with comparatively less attention given to the moral-economic architecture that distinguishes Islamic economics from a Shariah-compliant model of conventional finance. From the evidence of Bangladesh's perspective, particularly concentrating on the Islamic moral economics landscape and literature on governance, efficiency, and profitability, it suggests that the recent crisis was simultaneously structural and governance-driven and therefore a maqāṣid failure rather than a purely prudential mechanism. The article advances a four-part reform agenda, centralized and independent Shariah governance, a functioning sovereign sukuk and Islamic money market, activation of zakat, waqf, and Islamic microfinance, and inclusion-oriented Islamic fintech, as the route from scale to substance. The Bangladeshi case offers a cautionary and generative lesson for maturing Islamic finance jurisdictions from a global perspective.